(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation: Middle English (1100–1500 AD) represents the transitional period between Old English and Modern English, with its vocabulary reflecting a blend of historical, cultural, and linguistic influences. During this period, the lexicon, rooted in Anglo-Saxon, was enriched by the addition of Norman-French, Latin, and Scandinavian words. The diversity of regional dialects and the simplification of grammar contributed to the distinct characteristics of Middle English. Literary works, such as Geoffrey Chaucer’s The Canterbury Tales, serve as significant sources for understanding the vocabulary of this era.